Diabetic retinopathy and diabetic macular edema: prevalence in a family health care center of Antofagasta - Soto, Andrés; Cruz, Carla (Revista Chilena de Salud Pública, 2019)
Introduction: Diabetic retinopathy (DR) is a diabetic microangiopatic complication and the leading cause of blindness worldwide. The principal complication of DR is diabetic macular edema (DME). The objective of this study is to determine the prevalence of DR and their subtypes, as well as DME in a primary health care (PC) diabetic population of Antofagasta. Material and Methods: This is a transversal descriptive study carried out in a population of 380 diabetic patients diagnosed and treated in Antofagasta’s seven PC centers, who underwent an anual retinography for DR screening. The factors analyzed were sex, age, presence of RD and their subtypes, and DME. Results: We found a RD prevalence of 19.21%. In this group, the majority were men and the age group of 40-64 years showed the highest prevalence. The more frequent subtype (45.21%) was moderate non-proliferative DR, and the prevalence of DME was 1.84%. Conclusions: RD is a prevalent and preventable complication, and metabolic control programs and screening methods must be improved. This study contributes new data to the scarse national literature of this topic.